The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1414-81452008000300009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de fatores de risco de natureza modificável para a ocorrência de diabetes mellitus tipo 2

Abstract: Estudo transversal realizado com estudantes universitários do curso de Enfermagem para identificação de fatores de risco para o diabetes tipo 2. Em relação ao nível de risco: 65% apresentavam risco baixo, 27%, risco zero, enquanto 7,5% exibiam risco alto. A história familiar de diabetes e hipertensão foi identificada em 45% da amostra. A prevalência de sedentarismo foi igual a 75%; de sobrepeso, igual a 15%, e de obesidade (IMC e ³25 kg/m²), igual a 5%. Verificaram-se ainda um menor consumo de alimentos ricos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 1 publication
(2 reference statements)
4
8
1
5
Order By: Relevance
“…Studies conducted in Brazil reported rates similar to that of the present study, e.g. those found among nursing students in Rio de Janeiro, RJ 21 (20%), with 15% overweight and 5% obesity, and those among nutrition students in Dourado, MS (17%) 22 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Studies conducted in Brazil reported rates similar to that of the present study, e.g. those found among nursing students in Rio de Janeiro, RJ 21 (20%), with 15% overweight and 5% obesity, and those among nutrition students in Dourado, MS (17%) 22 .…”
Section: Discussionsupporting
confidence: 87%
“…As regards waist circumference (WC), found of students with increased cardiometabolic risk, defined as a WC greater than 80 for women and greater than 94 for men, the proportion found in the present study (10.3%) was lower than that obtained by Simon et al 18 among students in Lubango (21.4%), and by Vilarinho et al 21 among nursing students (15%).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Thus, this review suggests there are still few publications on T2DM in adolescents and children, but the progression of the disease becomes a major concern worldwide. As for college student, there were several factors of risk for T2DM [18][19]. Stressing [18] physical inactivity, overweight, obesity, high blood glucose and arterial hypertension, pointing to physical inactivity as the most prevalent risk.…”
Section: Discussionmentioning
confidence: 99%
“…Researches focused on identifying risk factors for T2DM were developed by nurses involving students, university students and health workers (5)(6)(7)(8)(9) , highlighting the need to extend the study to other populations, which will provide subsidy for planning interventions which contribute to reduce or delay the appearance of the disease.…”
Section: Introductionmentioning
confidence: 99%